The Impact of the Quality of then and TR Operating Conditions of Cars on Environmental Pollution (Texas Journal of Engineering and Technology, 2022)
The state and improvement of TEA at the level of ATP has a direct impact on the environmental safety of ATP. It is in ATP and other vehicle owners that storage, maintenance and TR of cars are carried out, their operability is restored and the bulk of production waste accumulates. The organization of production, the technologies used, the quality of maintenance and TR ultimately determine the technical condition, and hence the amount of harmful emissions. substances in the movement of cars and from production activities